Dynamics of rhinoceros beetles in different cropping area / Fudhail Hasif Azman - Azman, Fudhail Hasif (Faculty of Plantation and Agrotechnology, 2019)
The population of rhinoceros beetle (Oryctes Rhinoceros) were investigated in 3 different areas which is the oil palm (Elaeis guineensis) area contained coconut (Cocos nucifera) crop, durian (Durio) crop, and oil palm crop only by using pheromone trap. The research was conducted because the study wants to know if this crop contributes to the population of rhinoceros beetle. The objective of this research is to identify the different of rhinoceros beetle population between 3 different areas and their potential threat. The study was conducted by using 3 pheromone traps respectively in each area. 1 trap can cover 2 hectare, for coconut crop there are only 134 trees in this area, while for the durian crop there are only 45 trees. The data was collected twice a week about 5 weeks. Coconut area has large number of rhinoceros beetle which is 78 while the lowest is durian crop area which is 23. The average eggs for one rhinoceros beetle about 35 eggs. The conclusion is with the crop which is suitable for the rhinoceros breeding is forbidden in the oil palm area because it will contribute to the infestation of the rhinoceros beetle.